Development of Scheduling of Operating Rooms and Allocation of Inpatient Rooms Model by Considering Patient Preferences on Surgeon and Inpatient Room Classes - Valentina Sitanggang Febryanti; Nur Rosyidi Cucuk; Widyo Laksono Pringgo (E3S Web of Conferences, 2023)
Patient satisfaction on the services provided hospital indicates that hospital quality is improving. Surgery services and inpatient room services are two hospital health services that describe the hospital’s quality. This study proposed the development of an operating room scheduling model and inpatient room allocation based on the patient’s preference for surgeons and inpatient classes. Operating room scheduling and inpatient room allocation were optimized using Mixed Integer Linear Programming (MILP) and LINGO 18.0 software. The findings showed that the proposed model and algorithm could provide a feasible solution for minimizing hospital operating costs and maximizing patient preference. In order to obtain a satisfactory scheme for patients and hospitals, it was proposed to consider patient preferences in operating scheduling and inpatient room allocation